THE IMPERATIVES AND CHALLENGES OF ENSURING FOOD SECURITY OF SUBJECTS OF THE NORTH CAUCASUS MACRO-REGION - Tatiana Kulagovskaya; Galina Panaedova (Вестник Северо-Кавказского федерального университета)
In article the analysis of ensuring food security of subjects of the North Caucasian Federal District is carried out: loudspeakers of self-reliance and production of food, norms and the actual consumption of food, conclusions are drawn on differentiation of consumption on subregions, recommendations about strengthening of food security are made and carrying out expeditious regional monitoring and definition of system of indicators of assessment comparable to the systems of the international level is offered.